A meta-methodology to enhance pluralist qualitative research: One man's use of socio-sexual media and midlife adjustment to HIV. Issue 10 (3rd October 2018) - Madill, Anna; Flowers, Paul; Frost, Nollaig; Locke, Abigail
Abstract : Aim: Our aim is to offer and illustrate a novel meta-methodology to enhance the rigour of method selection and understanding of results in pluralist qualitative research (PQR). Method: To do so, we make innovative use of articulation of four discrete dimensions characterising different forms of thematic analysis. We provide secondary analyses of an interview from the Social Media, Men who have Sex with Men and Sexual Health project using critical discursive psychology, dialogical analysis, interpretative phenomenological analysis and psychosocial narrative analysis. Results: All four methods identified aspects of three central foci: Compartmentalisation, Detachment and Jouissance. Conclusion: We discuss how our proposed meta-methodology provides a rationale for the selection of methods in a PQR, offer evidence that it can anticipate the relative similarity in focus of the methods employed, and argue that our meta-methodology reveals the possibility of identifying an 'axial' or 'hub' method of a PQR which might be particularly fruitful in exploring commonalities and differences in results. Finally, we examine the synergies and challenges of combining pairs of the methods we used.